Assessment of mutual aid older care needs for older adults with multimorbidity in urban China: a Kano model-based study - Zhang, Zhe; Chen, Yongqian; Ochoa, Marcos C. (Frontiers in Public Health, 2025)
BackgroundChina faces escalating challenges in older care because of rapid population ageing and the high prevalence of multimorbidity among urban older adults. Traditional family-based and institutional care models are increasingly inadequate, necessitating innovative solutions like mutual aid older care. However, research gaps persist in understanding the prioritised needs of urban older with multimorbidity within mutual aid older care frameworks. This study evaluates and prioritises mutual aid older care needs for older adults with multimorbidity in urban Chinese communities, by integrating Maslow’s Hierarchy of Needs with the Kano Model.MethodsA cross-sectional survey was conducted among 240 older adults (aged ≥65, with ≥2 chronic conditions) across 25 urban communities in Hefei, China. Using a validated questionnaire, 43 service items across safety/health, daily life, learning/socialisation, spiritual, and entertainment domains were assessed. Kano Model categorisation and better-worse coefficient analysis were applied to classify needs (must-be, one-dimensional, attractive, indifferent) and rank priorities via sensitivity calculations.ResultsKey must-be needs included cooking, washing hair, and psychological counselling, while one-dimensional priorities emphasised exercise and travelling. Attractive needs featured telemedicine and cultural activities (e.g., Red Song Club). Indifferent items, such as pest control, had minimal impact on satisfaction. The analysis highlighted the centrality of physical health services, mental health support, and social engagement in enhancing quality of life.DiscussionUrban older adults with multimorbidity prioritise integrated care models addressing both basic survival needs and higher-order psychosocial well-being. Mutual aid older care frameworks must therefore balance healthcare accessibility with opportunities for social participation and emotional fulfilment. Future policies should adopt evidence-based, culturally tailored strategies to optimise resource allocation and foster sustainable ageing-in-place solutions. Limitations include geographic specificity and cross-sectional design, warranting broader longitudinal and mixed-method research.